Data for paper "Heterogeneity Induces Spatiotemporal Oscillations in Reaction-Diffusions Systems" - Krause, A; Gaffney, E (University of Oxford, 2018)
All data were created using Comsol as described in the paper. The .csv files can be loaded and plotted via Matlab, and the .m files should function as runnable scripts. Each Figure has its own folder containing data sufficient to reproduce the Figure.